Cenozoic deformation and exhumation history of the Central Kyrgyz Tien Shan. Issue 2 (25th February 2014) - Macaulay, Euan A.; Sobel, Edward R.; Mikolaichuk, Alexander; Kohn, Barry; Stuart, Finlay M.
Abstract New low‐temperature thermochronological data from 80 samples in eastern Kyrgyzstan are combined with previously published data from 61 samples to constrain exhumation in a number of mountain ranges in the Central Kyrgyz Tien Shan. All sampled ranges are found to have a broadly consistent Cenozoic exhumation history, characterized by initially low cooling rates (<1°C/Myr) followed by a series of increases in exhumation that occurred diachronously across the region in the late Cenozoic that are interpreted to record the onset of deformation in different mountain ranges. Combined with geological estimates for the onset of proximal deformation, our data suggest that the Central Kyrgyz Tien Shan started deforming in the late Oligocene‐early Miocene, leading to the development of several, widely spaced mountain ranges separated by large intermontane basins. Subsequently, more ranges have been constructed in response to significant shortening increases across the Central Kyrgyz Tien Shan, notably in the late Miocene. The order of range construction is interpreted to reflect variations in the susceptibility of inherited structures to reactivation. Reactivated structures are also shown to have significance along strike variations in fault vergence and displacement, which have influenced the development and growth of individual mountain ranges. Moreover, the timing of deformation allows the former extent of many intermontane basins that have since been partitioned to be inferred; this can be linked to the highly time‐transgressive onset of late Cenozoic coarse clastic sedimentation.